Annual variations of vitamin D levels and exercise capacity in Italian amateur cyclists - Ferrari, P.; Meneghello, M.; Zamboni, F.; Schenk, K.; Ferrari, M. (Medicina dello Sport, 2020)
BACKGROUND: There are few studies on circulating levels of Vitamin D in amateur athletes, even though the concentrations of the hormone might influence the performance. Aim of this study was to measure circulating levels of 25-hydroxy-cholecalciferol (25(OH)D) in a group of non-professional cyclists, correlating hormone concentrations with physical performance and ventilatory efficiency. METHODS: Thirty-seven male cyclists were tested before (March) and at the end (September) of competitive season. In both occasions, 25(OH)D and parathyroid hormone (PTH) serum levels, body composition were measured, and maximal cardiopulmonary exercise tests (CPET) was performed. During CPET, oxygen consumption (VO2, L/min), CO2 production (VCO2, L/min), ventilation (VE, L/min), VE/VO2, and VE/VCO2 at the peak of exercise were measured. RESULTS: In March, 25(OH)D levels (14.9±6.5 ng/mL) were lower than normal range in all participants, and elevated levels of PTH was found in 13 athletes. At September, hormone concentrations were higher (38.5±10.6 ng/mL), even if they were lower than normal range in nine cyclists. No relationship was found between 25(OH)D levels and VO2 at the peak of exercise, either at the beginning or at the end of the season. In March, a negative relationship was found between 25(OH)D, VE/VCO2 (r=-0.363; P=0.027) and VE (r=-0.362; P=0.028) at the peak of exercise. CONCLUSIONS: In athletes practicing outdoor sports, hypovitaminosis D, often associated with increased PTH concentration, are frequent findings. Furthermore, hormone levels do not correlate with aerobic power parameters, but they are inversely associated with maximal VE/VCO2 and VE, suggesting a modulating effect of vitamin D on ventilation.